Conceptualising Gifted Student (Dis) Engagement through the Lens of Learner (Re) Engagement - Michelle Ronksley-Pavia; Michelle M. Neumann (MDPI AG, 2020)
It is well-recognised that disengagement is a growing problem in schools across the globe. Furthermore, statistics show that nearly 60% of all gifted students are not actualising their potential, exposing the loss of potential for both the individual and society. While disengagement and underachievement are complex issues with no one root cause, it is well-established that when students are actively engaged in their learning, they learn more effectively. Talent actualisation is not guaranteed just because a student is gifted. As such there is heightened concern about student (dis)engagement, where there is a failure to adequately support (re)engagement so that gifted potential can develop into talent actualisation, which is evidenced through mastery. This conceptual article provides a new lens through which to explore (re)engagement opportunities for gifted students by conceptualising the interrelationship between three interconnected constructs: (1) four engagement dimensions (behavioural, affective, social, and cognitive); (2) Neihart and Betts' six profiles of the gifted; and (3) appropriate pedagogical approaches aimed at (re)engagement. The authors' focus on proposing new conceptualisations of these three interdependent constructs through a framework titled the (Re) Engagement Nexus Model. This model is intended as a starting point for future research in personalising (re)engagement opportunities for gifted learners and preventing underachievement and disengagement before it becomes entrenched.